Informacijske zasnove evidenc o nepremičninah - Mladenovič, Uroš (Geodetski vestnik, 1997)
The basic geocoded records play an important role in efforts to set up registers of real estate. The ability to reach the goal depends on the organisational and instutional efforts and no longer on information technology.
Keywords: geodezija; GIS; informacijski sistemi; informatika; organizacija